Inequality and migration: A behavioral link - Oded Stark (University of Warsaw, Centre of Migration Research (CMR), 2005)
We provide an analytical-behavioral explanation for the observed positive relationship between income inequality, as measured by the Gini coefficient, and the incentive to migrate. We show that a higher total relative deprivation of a population leads to a stronger incentive to engage in migration for a given level of a population's income; that total relative deprivation is positively related to the Gini coefficient; and that, consequently, the Gini coefficient and migration are positively correlated, holding the population's income constant.
Keywords: 330; Income inequality; Relative deprivation; The Gini coefficient; The incentive to migrate; Einkommensverteilung; Gini-Koeffizient; Migrationsforschung